Analisis Strategi Pemasaran PT Bali Coklat (Pod Chocolate) - EDSA, INDY; SUSRUSA, KETUT BUDI; DEWI, IDA AYU LISTIA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.12, No.1, Juli 2023, 2023)
Marketing Strategy Analysis of Bali Coklat (Pod Chocolate) In the midst of competition, Bali Coklat needs a strategy to attract market attention by creating products according to their demands. Diverse market demands require company to use marketing target strategy hence the effective services can be deployed in the target market. This study discussed the process of market segmentation, targeting, and determining the market position to generate a marketing strategy based on the marketing mix. Data collection through questionnaires was distributed to 100 consumers of Pod Chocolate in Badung Regency with non-probability random sampling. This quantitative descriptive study used cluster analysis, correspondence analysis, and multidimensional scaling in SPSS and Microsoft Excel. Market segmentation which are based on demographics, consumer behaviours and psychographics forms three segments. Segment-1 is the target market which has the largest size, very positive appeal and been classified as active, modern, optimistic, and established in psychographics. The market position shows Delicacao as the company's closest competitor but has no resemblance to other similar companies when is viewed from product attributes. Pod Chocolate has superiority in quality, safety, variety, store and impression while packaging, taste, price, discounted prices and advertising can still be improved thus the marketing mix strategy will be implemented to those attributes.